Host-Parasite-Bacteria Triangle: The Microbiome of the Parasitic Weed Phelipanche aegyptiaca and Tomato-Solanum lycopersicum (Mill.) as a Host - Iasur Kruh, Lilach; Lahav, Tamar; Abu-Nassar, Jacline; Achdari, Guy; Salami, Raghda; Freilich, Shiri; Aly, Radi (Frontiers in Plant Science, 2017)
Broomrapes (Phelipanche/Orobanche spp.) are holoparasitic plants that subsist on the roots of a variety of agricultural crops, establishing direct connections with the host vascular system. This connection allows for the exchange of various substances and a possible exchange of endophytic microorganisms that inhabit the internal tissues of both plants. To shed some light on bacterial interactions occurring between the parasitic Phelipanche aegyptiaca and its host tomato, we characterized the endophytic composition in the parasite during the parasitization process and ascertained if these changes were accompanied by changes to endophytes in the host root. Endophyte communities of the parasitic weed were significantly different from that of the non-parasitized tomato root but no significant differences were observed between the parasite and its host after parasitization, suggesting the occurrence of bacterial exchange between these two plants. Moreover, the P. aegyptiaca endophytic community composition showed a clear shift from gram negative to gram-positive bacteria at different developmental stages of the parasite life cycle. To examine possible functions of the endophytic bacteria in both the host and the parasite plants, a number of unique bacterial candidates were isolated and characterized. Results showed that a Pseudomonas strain PhelS10, originating from the tomato roots, suppressed approximately 80% of P. aegyptiaca seed germination and significantly reduced P. aegyptiaca parasitism. The information gleaned in the present study regarding the endophytic microbial communities in this unique ecological system of two plants connected by their vascular system, highlights the potential of exploiting alternative environmentally friendly approaches for parasitic weed control.